The art of not making : the new artist/artisan relationship - Petry, Michael, 1960- (Thames & Hudson, 2011)
When art meets craft -- Glass -- Metal -- Stone -- Textiles -- Other materials -- Interviews
Keywords: obrazové publikace; pictorial works; 1951-2010; umělecká díla; výtvarné materiály; užité umění; umělecká řemesla; moderní umění -- 1951-2010; art works; artistic materials; applied arts; arts and crafts; modern art -- 1951-2010